Readiness Of Women Aged 45-55 Years In Facing The Menopause: A Literature Review - Yani, Tri Ardayani (Sahabat Publikasi Kuu, 2025)
Menopause is a transitional phase from the reproductive period to the non-reproductive period which is marked by the cessation of menstruation. Women generally experience menopause between the ages of 45 and 55 years. The World Health Organization (WHO) estimates that by 2030 there will be around 1.2 billion women aged over 50 years. The Health Service of the Republic of Indonesia stated that by 2025, the number of menopausal women in Indonesia is estimated to be 60 million. Women experiencing menopause experience signs and symptoms both physiologically and psychologically. Menopausal syndrome affects women all over the world. It is estimated that 70-80% of women in Europe experience this syndrome, followed by 60% in America, 57% in Malaysia, 18% in China and 10% in Japan and Indonesia experience this syndrome. Women's lack of readiness in facing menopause is one of the factors that will influence behavior in facing menopause. Women can prepare themselves by increasing their knowledge about health and controlling the changes that will occur during menopause. To identify the readiness of women aged 45-55 years to face menopause. This paper was written using a literature review methodology. The search terms “readiness” and “menopausal women” were used in the review literature search approach. The information used to search for publications both domestic and foreign comes from relevant sources, especially Pubmed and Google Scholar. (1) Articles must be published within the last five years (2020–2024), (2) must be original, (3) must be fully accessible, and (4) must be in English or Indonesian. Based on the search results, 9 national articles were obtained. These articles highlight the potential readiness of women aged 45-55 years to face menopause. A woman's readiness to face menopause will really help a woman to face this period better. Physical and psychological readiness is very necessary to face the menopause period.